The impact of refugee experiences on education: Evidence from Burundi - Sonja Fransen; Carlos Vargas-Silva; Melissa Siegel (IZA Journal of Development and Migration, 2018)
Previous studies suggest that displacement is one of the channels through which conflict impacts schooling outcomes. However, there is scarce evidence on this impact for those who are displaced internationally (i.e. refugees). We use data from Burundi, a country which experienced large-scale conflict-led emigration and substantial post-war refugee return, to explore differences in schooling outcomes between returnees, defined as individuals who were displaced to a neighbouring country and later returned home, and stayees, defined as individuals who never left the country during the conflict (i.e. those who were never displaced and those who were only displaced internally). Our results suggest that, controlling for pre-war characteristics and cohort effects, returning refugees are more likely to have finished primary school than their contemporaries who never left the country. We also find that an additional year spent as a refugee while of schooling age is associated with a four to six percentage point increase in the likelihood of finishing primary school.
Keywords: F22; D74; I25; 330; Refugees; Education; Africa